Analisis Audit Kasus Manipulasi Laporan Keuangan PT Wanaartha Life Tahun 2023 - Adelia Furry Avriandi; Apriana Nur Asyifa; Giyan Triyani Sari; Maharani Dara Dinanti; Sandra Audina Maharani; Herlina Manurung (Jurnal Akuntan Publik, 2025)
This study aims to examine the practice of financial statement manipulation that occurred at PT Wanaartha Life in 2023. This case emphasizes the importance of transparency and integrity in corporate financial reporting. The practice of manipulating financial statements is considered unethical and often occurs due to various motivations, including pressure to achieve financial targets and maintain the company's reputation. Violations of the professional code of ethics can have a negative impact on society, because members of the profession who do not comply with established rules and values can result in a loss of trust and respect for the profession. The research method used in this research is a literature study, where this research produces descriptive data findings, in the form of words based on the results of observations. The results showed that the company's financial statements lacked integrity and transparency in financial reporting.